2013
DOI: 10.1007/s00540-013-1763-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ropivacaine concentrations after ultrasound-guided transversus abdominis plane block for open retropubic prostatectomy

Abstract: Ropivacaine concentration did not alter pharmacokinetic profile following TAP blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…In the rectus sheath group, a gradual elevation in plasma levobupivacaine concentration was seen, and the time to peak concentration (Tmax) was more than double that in the TAP group. Previous studies on the rise in plasma ropivacaine concentration reported that Tmax was 23.1 min and 48.5 min after TAP block and rectus sheath block , respectively. Similarly, another study reported that Tmax of ropivacaine was 35 min and 53 min after TAP and rectus sheath block, respectively.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the rectus sheath group, a gradual elevation in plasma levobupivacaine concentration was seen, and the time to peak concentration (Tmax) was more than double that in the TAP group. Previous studies on the rise in plasma ropivacaine concentration reported that Tmax was 23.1 min and 48.5 min after TAP block and rectus sheath block , respectively. Similarly, another study reported that Tmax of ropivacaine was 35 min and 53 min after TAP and rectus sheath block, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Kitayama et al proposed two possible explanations for the different changes in plasma concentrations of local anaesthetics after TAP and rectus sheath blocks. One of the explanations is that in a TAP block, local anaesthetics are readily absorbed into the blood stream because they are injected into the neurovascular plane between the internal oblique and transversus abdominis muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Of these instances, three patients exhibited subjective symptoms of mild LA systemic toxicity. 21 Symptoms were limited to perioral and tongue paraesthesia, a metallic taste, and slurred speech. No instances of severe neurotoxicity (seizures) or persistent cardiovascular instability were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies measured systemic concentrations of LA agents after bilateral USG TAPB (Table 2). Abdominal or pelvic surgery was performed in eight studies, [18][19][20][21][22][23][24][25] while in the remaining three studies participants were healthy volunteers who did not undergo any surgery. [26][27][28] Eight of the 11 studies used ropivacaine.…”
Section: Transversus Abdominis Plane Blockmentioning
confidence: 99%
“…The early absorption speed of ropivacaine can be affected by ropivacaine-induced vasoconstriction. However, a study examining the effects of various ropivacaine concentrations (0.25%, 0.5%, and 0.75%) on pharmacokinetic profiles following transversus abdominal plane did not find any difference among the concentrations 19. The mean half-time of the rapid absorption is approximately 14 minutes, while the mean absorption half-time of the slower phase is approximately 4.2 hours 20.…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 94%